The factors influencing training effectiveness at Jabatan Ketua Menteri Melaka / Hazilah Uzir - Uzir, Hazilah (Faculty of Business and Management, 2012)
Background: Training play an important role in increasing employee knowledge, skills and performance. Training will be effective when the employees understand clearly what they learn in the training program and can apply the learning at the workplace. The purpose of this study was to identify the factors influencing the training effectiveness which are whether or not commitment management, trainer’s capability and training content can affect the effectiveness of training program. This paper also investigate the main factors can effect the effectiveness of training program.